A new methodology for measuring land fragmentation - Demetriou, Demetris; Stillwell, John; See, Linda (My University, 2013)
The presence of land fragmentation can indicate that an existing land tenure structure is problematic. It can be a major problem in many regions because it restricts rational agricultural development and reduces the opportunities for sustainable rural development although in some cases, it can prove beneficial and desirable for social and environmental reasons. Whilst policies to counter land fragmentation require reliable measurement of the situation, current fragmentation indices have significant weaknesses. In particular, they ignore critical spatial variables such as the shape of parcels as well as non-spatial variables such as ownership type and the existence or absence of road access for each land parcel. Furthermore, there is no flexibility for users to select the variables that they think appropriate for inclusion in the fragmentation index, and no variable weighting mechanism is available. The aim of this paper is to introduce a new 'global land fragmentation index' that combines a multi-attribute decision-making method with a geographic information system. When applied to a case study area in Cyprus, the new index outperforms the existing indices in terms of reliability as it is comprehensive, flexible, problem specific and knowledge-based. The methodology can be easily applied to assess the quality of any existing system for which evaluation criteria can be defined with values ranging from the worst to best conditions. © 2013 Elsevier Ltd.
Keywords: Global land fragmentation index; Land fragmentation; Multi-attribute decision-making method; Value functions